PEOPLE PEDAGOGY VOSITASIDA O‘IN THE PEOPLE MORAL EDUCATION FORMATION - Khudoiberdiyeva Shoira Khushvaqt qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This in the article o'of the birds moral his upbringing _ appearances, moral of education o'ziga specific properties and uni develop people pedagogy through instead increase, o'students ongiga national tradition - our habits absorb through competent generation bo`lib reach about so'z goes